New Times, New Families: From Legitimacy to Affectivity - Rodrigues, Edwirges Elaine; Alvarenga, Maria Amália de Figueiredo Pereira [UNESP] (My University, 2021)
Increasingly, the idea of family distances itself from the matrimonial structure. In this way, the affection was recognized as an embryonic element of family structures, becoming a legal value. Thus, in the search for the concept of family entity, it is necessary to have a pluralist view, which houses the most diverse living and affective models. This way, the Federal Constitution of 1988 recognizes, in addition to the matrimonial family, the families constituted by the common-law marriage and the single-parent families, granting them legal protection. Furthermore, the express mention of such families does not mean the exclusion of other family arrangements, such as the mosaic family, the multiparental family, the no-parents family, the unilinear family, the homosexual family, the simultaneous family and the multi-affective family, all of them having the same constitutional protection and not being allowed to stay outside the jurisdictional tutelage.
Novos tempos, novas famílias: da legitimidade para a afetividade
Keywords: affectivity; family law; New family arrangements